Small mammal communities in the transformed landscapes of the Western Cape lowlands and their role in alien invasion into fynbos remnants - Mugabe, Chapangara James (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--Stellenbosch University, 2008.